2003
DOI: 10.1051/0004-6361:20030466
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectrum of the planetary nebula M 2-24

Abstract: Abstract.We have obtained medium-resolution, deep optical long-slit spectra of the bulge planetary nebula (PN) M 2-24. The spectrum covers the wavelength range from 3610-7330 Å. Over two hundred emission lines have been detected. The spectra show a variety of optical recombination lines (ORLs) from C, N, O and Ne ions. The diagnostic diagram shows significant density and temperature variations across the nebula. Our analysis suggests that the nebula has a dense central emission core. The nebula was thus studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
(60 reference statements)
2
36
1
Order By: Relevance
“…Clearly emission of these diagnostic lines is dominated by the surrounding diffuse nebula. A similar result has been found in the peculiar bulge PN M 2-24 (Zhang & Liu 2003). Thus the possibility of a dense symbiotic nebula embedded in the low-N e ionized region of Me 1-1 cannot be completely ruled out.…”
Section: Discussionsupporting
confidence: 80%
“…Clearly emission of these diagnostic lines is dominated by the surrounding diffuse nebula. A similar result has been found in the peculiar bulge PN M 2-24 (Zhang & Liu 2003). Thus the possibility of a dense symbiotic nebula embedded in the low-N e ionized region of Me 1-1 cannot be completely ruled out.…”
Section: Discussionsupporting
confidence: 80%
“…The large uncertainty of ADF(N 2+ ) is due to the large uncertainty in the CEL N 2+ abundance. ADF(O 2+ ) in M1-11 is comparable to that of high-density PN M2-24 (namely, 17;Zhang & Liu 2003). The density structure for M1-11 is similar to that of M2-24, showing a large density contrast of n e = 10 3−6 cm −3 .…”
Section: Rl Ionic Abundancesmentioning
confidence: 61%
“…Effective recombination coefficients for the lines' parent multiplet are the same as those used by Otsuka et al (2010). The RL ionic abundances are insensitive to the electron density under 10 8 cm −3 (Zhang & Liu 2003). For the ionic abundance calculations, we therefore adopted the effective recombination coefficients in case of n e = 10 4 cm −3 for C 2+ and N 2+ .…”
Section: Rl Ionic Abundancesmentioning
confidence: 99%
“…This extremely low total helium abundance can be explained by the fact that a significant amount of He 0 is expected to be present in a low‐excitation nebula like NGC 40, and He 0 was not considered in the He/H given above. To circumvent this kind of problem, Zhang & Liu (2003) suggested that an ICF based on the S + and S ++ abundances can be used to account for the He 0 abundance of low‐ excitation PNe. Using our own data we were not able to calculate a S ++ abundance map, nevertheless, if we consider the S ++ abundances found by Pottasch et al (2003) and Liu et al (2004b) (Table 8), and the mean value of the S + /H + map that we calculated (8.88 × 10 −7 , in Table 8), we can determine a more reliable value for the He total abundance of NGC 40.…”
Section: Mapping Resultsmentioning
confidence: 99%